Fatores determinantes de permanencia e evasão de funcionarios de uma organização - Medina, João Bosco (1987)
The study intends to give its contribution to a better understanding of the problerns of why the Central Bank of Brazil ernployees are leaving their job. Adrnitting the idea that the decision of the employees to rema in in the Bank is based on three points: job satisfaction, satisfaction with the reward system anq une influence of the externai environment, the study intended to determine the factors of those elements being able to influence the ~ecision to remain or to leave. Two kinds of analysis were used: the descriptive and the contingencial. The first one was designed to introduce the sample characteristics and the externai environmental factors associated with remaining in the Bank or leaving. The second one was designed to determine the rnain causes that can better explain 'the job satisfaction and the reward system. One of the study's conclusions: there is a large yearning on the part of the employees to take part in the effecti ve organizational life, that means not only in hearing and being heard when defining the organizational goals and guidelines, as well as in being able to plan and to implernent their carreers. It is hoped that the analysis made can be, used to rethink the yearnings, doubts, frustrations and achievernents of the employees in the organizational context in which, in the wide meaning oi the word, they'live.